2016
DOI: 10.1111/hepr.12689
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of combined triple therapy comprising two types of peginterferon with simeprevir in patients with hepatitis C virus genotype 1b

Abstract: Peginterferon α2a or α2b in combination with SMV + ribavirin therapy showed identical antiviral effects in patients with chronic hepatitis C. Also, the incidence of adverse events was identical for both regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…From 2014, an interferon‐free therapy using DAAs, achieving a near 100% SVR, was introduced in clinical practice 25 . Several studies have corroborated the clinical utility and safety of DAA therapy, which can eliminate HCV without remarkable adverse drug events 26–29 . Notably, these promising therapies 30 have further decreased deaths due to HCV infection in Japan, and this trend is expected to continue into the future.…”
Section: Discussionmentioning
confidence: 99%
“…From 2014, an interferon‐free therapy using DAAs, achieving a near 100% SVR, was introduced in clinical practice 25 . Several studies have corroborated the clinical utility and safety of DAA therapy, which can eliminate HCV without remarkable adverse drug events 26–29 . Notably, these promising therapies 30 have further decreased deaths due to HCV infection in Japan, and this trend is expected to continue into the future.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2011, direct‐acting antiviral (DAA) regimens with pegylated interferon (PEG‐IFN)‐α and ribavirin (RBV) have been approved for anti‐HCV therapy in patients with chronic HCV genotype 1 infection, and these regimens achieve a higher sustained virological response (SVR) rate than conventional interferon (IFN)‐based therapy . However, PEG‐IFN‐α and RBV are associated with adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several highly effective, albeit expensive, direct‐acting antiviral (DAA) treatments have been developed to eliminate HCV infection by directly affecting the enzymatic activity of the HCV. Many clinical studies reported effectiveness, safety, and impact on patients’ quality of life (QOL) of DAA . However, concerns have been raised regarding the cost‐effectiveness of expensive medical technologies, and their burden on Japan's health insurance system.…”
Section: Introductionmentioning
confidence: 99%